2022
DOI: 10.3389/fgene.2022.821587
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biallelic Variant in the BRAT1 Gene Caused Nonprogressive Cerebellar Ataxia Syndrome

Abstract: Recessive mutations in BRAT1 cause lethal neonatal rigidity and multifocal seizure syndrome (RMFSL), a phenotype characterized by neonatal microcephaly, hypertonia, and refractory epilepsy with premature death. Recently, attenuated disease variants have been described, suggesting that a wider clinical spectrum of BRAT1-associated neurodegeneration exists than was previously thought. Here, we reported a 10-year-old girl with severe intellectual disability, rigidity, ataxia or dyspraxia, and cerebellar atrophy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Except for pneumonia, the clinical features of the proband in this study were comparable to typical characteristics of RMFSL. Although RMFSL has been reported in different populations, to our knowledge, RMFSL is less common among the Chinese population with only four cases reported to date (Burgess et al, 2019;Li et al, 2021;Qi et al, 2022;Van Ommeren et al, 2018). In 2018, Van et al described for the first time a female newborn affected by RMFSL with homozygous BRAT1 mutation variant c.1395G>C born to non-consanguineous Chinese parents (Van Ommeren et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for pneumonia, the clinical features of the proband in this study were comparable to typical characteristics of RMFSL. Although RMFSL has been reported in different populations, to our knowledge, RMFSL is less common among the Chinese population with only four cases reported to date (Burgess et al, 2019;Li et al, 2021;Qi et al, 2022;Van Ommeren et al, 2018). In 2018, Van et al described for the first time a female newborn affected by RMFSL with homozygous BRAT1 mutation variant c.1395G>C born to non-consanguineous Chinese parents (Van Ommeren et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since the BRAT1 was first reported as the causative gene of RMFSL (Puffenberger et al, 2012), 45 mutations in the BRAT1 have been reported to date according to the Human Gene Mutation Database HGMD (http://www.hgmd.org/; Professional 2022.1) and the existing literature, including 20 missense/nonsense mutations, 8 splice mutations, 9 small deletions, 5 small insertions/duplications, and 3 gross deletions mutations (Figure 5, Table 1) (Capalbo et al, 2019;Colak et al, 2020;Fernández-Jaén et al, 2016;Hanes et al, 2015;Heide et al, 2020;Li et al, 2021;Na et al, 2020;Qi et al, 2022;Scheffer et al, 2020;Szymańska et al, 2018;Wu et al, 2021). In this study, we found a sixth splice site mutation c.431-2A>G (Colak et al, 2020;Horn et al, 2016;Srivastava et al, 2014;Stödberg et al, 2020;Rudolf et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…RNA sequencing was performed by Aegicare, which has been described in our previous literature ( Qi et al, 2022 ). Total RNA was extracted from peripheral blood samples of one of the carriers (I-2) and two normal females using a Qiagen blood RNA extraction kit I (QIAGEN, United States) according to the manual.…”
Section: Methodsmentioning
confidence: 99%